Halogen-free flame-retardant heat-resistant color-changing nylon and preparation method thereof
The halogen-free flame-retardant heat-resistant color-changing nylon material addresses PA66's poor flame retardancy and thermal discoloration by modifying the resin with unsaturated organic dibasic acids and forming a dense carbon layer, enhancing safety and appearance stability.
Patent Information
- Application Number
- CN202411411242.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Nylon 66 (PA66) exhibits poor flame retardancy, generates excessive heat and smoke during burning, and undergoes thermal discoloration due to oxidative decomposition, posing safety and appearance risks, especially in high-temperature environments.
A halogen-free flame-retardant heat-resistant color-changing nylon material is prepared by modifying PA66 resin with unsaturated organic dibasic acids, incorporating a halogen-free flame retardant compound, and adding a heat stabilizer and high-temperature resistant color powder, forming a dense carbon layer and chelating aluminum ions to reduce thermal discoloration.
The material achieves enhanced flame retardancy, improved thermal discoloration resistance, and increased notched impact strength, ensuring safety and appearance stability in high-temperature conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to nylon materials, in particular to a halogen-free flame-retardant heat-resistant color-changing nylon and a preparation method thereof. Background Art
[0002] Nylon 66 (PA66) is a semi-crystalline thermoplastic polymer made by polycondensation of adipic acid and hexamethylenediamine. It is widely used in modern industry due to its excellent mechanical and electrical properties, high chemical resistance and wear resistance, and easy processing. However, PA66 has a high methylene content, which leads to poor flame retardancy. It produces a lot of heat and smoke when burning, and the dripping of the burning PA66 melt promotes the further spread of the fire, thus bringing a high safety risk. Therefore, it is necessary to prepare PA66 with higher flame retardancy.
[0003] Among the many halogen-free flame retardants, phosphorus compounds have become the focus of research due to their low smoke generation rate. Among them, aluminum hypophosphite will decompose into phosphates when heated, and these phosphates can react with the PA66 matrix to form a carbon layer. Although these carbon layers can effectively slow down the transfer of oxygen and heat into the material and inhibit the combustion process, the formation efficiency of the complete carbon layer is slow, which will limit the final flame retardant effect.
[0004] In addition, with the expansion of the application scope of PA66 materials, especially in the application of some light-colored special parts in the home appliance industry, people have begun to have higher requirements for the appearance of parts while considering the service life and functionality of the parts. For example, in some long-term high-temperature environments, PA66 is required to have excellent heat-oxidative aging resistance, ensure the stability of the structural dimensions of the parts, and have excellent heat-discoloration resistance.
[0005] The fact that nylon is prone to thermal oxygen aging and discoloration is determined by its own structure. Oxygen will attack the carbon atom at the α position of the -NH- group, triggering a free radical oxidative decomposition reaction, causing the nylon molecule to break and produce chromophores, which will not only reduce the mechanical properties of the material, but also cause the surface of nylon products to turn yellow. As the aging time increases, it will even turn into dark brown, seriously affecting the appearance of the product. This is unacceptable for the home appliance industry, which has strict requirements on the appearance of products.
[0006] Therefore, there is an urgent need to study a nylon material with excellent flame retardant effect and heat discoloration resistance. Summary of the invention
[0007] Based on the problems of the prior art, the present invention provides a halogen-free flame-retardant heat-resistant color-changing nylon material and a preparation method thereof.
[0008] A halogen-free flame-retardant heat-resistant color-changing nylon material comprises the following raw materials by mass percentage: 40-77% of modified PA66 resin, 10-20% of modified glass fiber, 10-30% of a halogen-free flame retardant compound, 1-3% of an antioxidant, 1-3% of a heat stabilizer, and 1-5% of a high-temperature resistant color powder; wherein the modified PA66 resin is a polymer obtained by modifying a PA66-6T copolymer with an unsaturated organic dibasic acid, and the halogen-free flame retardant compound comprises ammonium polyphosphate, aluminum hypophosphite and aluminum oxide.
[0009] In some embodiments of the present invention, the method for preparing the modified PA66 resin comprises the following steps: S1: Weigh terephthalic acid and adipic acid and put them into a reactor, add deionized water, control the temperature of the reactor at 30-60°C, then dissolve hexamethylenediamine in an equal molar amount to the two dibasic acids in deionized water, heat to an isothermal state with the reactor, add it into the reactor and react for 30-45 minutes; S2: After the reaction is completed, hot filtration is performed, and the filtrate is taken for rotary evaporation until crystals are precipitated. After multiple recrystallizations and water washing, the solid sample is placed in a vacuum oven for drying to obtain a PA66-6T copolymer; the surface of the obtained PA66-6T copolymer is cleaned and impurities are removed; S3: Add ultrapure water, the treated PA66-6T copolymer, and the initiator into another reactor, stir and mix well, then add the unsaturated organic dibasic acid, react at 50-57°C for 1-1.5h, add the initiator again, react for a predetermined time and then stop the reaction, filter out the mother liquor in the reaction system, extract the obtained solid with boiling water for 2.5-3h, filter out the clear liquid again, and vacuum dry the obtained product to obtain the modified PA66 resin.
[0010] Furthermore, the initiator in S3 is a mixture of sulfuric acid and potassium persulfate, and in the reaction system, the concentration of sulfuric acid is 0.5-0.6 mol / L, and the concentration of persulfate is 10-20 mmol / L.
[0011] Furthermore, the unsaturated organic dibasic acid in S3 is one of 2-propyl-2-butenedioic acid, 4-ethyl-2-pentenedioic acid, 3-hexenedioic acid, 5-methyl-2-hexenedioic acid, 3-methyl-2-hexenedioic acid, 4-isopropyl-2-hexenedioic acid, and 5-methyl-2-heptenedioic acid, and the concentration in the reaction system is 1.6-2.2 mol / L.
[0012] In some embodiments of the present invention, the preparation method of the modified glass fiber comprises the following steps: mixing deionized water, anhydrous ethanol and aminosilane coupling agent in a mass ratio of 100:100:2-4 to prepare a surface modification liquid; loading the surface modification liquid into an ultrasonic disperser, introducing the glass fiber into the ultrasonic dispersion for 1-2 hours; taking out the treated glass fiber, rinsing it with deionized water, and drying it to obtain the modified glass fiber.
[0013] In some embodiments of the present invention, the mass ratio of the surface modification liquid to the glass fiber is 10-12:1.
[0014] In some embodiments of the present invention, in the halogen-free flame retardant compound, the mass ratio of ammonium polyphosphate, aluminum hypophosphite and aluminum oxide is 5:8:1-2.
[0015] In some embodiments of the present invention, the heat stabilizer comprises at least one of barium stearate, barium palmitate, barium oleate, barium laurate and barium myristate.
[0016] In some embodiments of the present invention, the high temperature resistant toner comprises at least one of a cobalt blue pigment and a cobalt green pigment.
[0017] In the present invention, PA66 is first copolymerized and modified, and part of the tetramethylene in adipic acid is replaced by the benzene ring in terephthalic acid, and then the carbon-carbon double bond is subjected to an addition reaction with the -NH- in the amide bond to introduce a carboxyl group into the copolymerized and modified PA66 chain. The increase in the benzene ring content in the molecular chain brought about by the copolymerization modification can increase the notch impact of the modified PA66 resin. The introduced carboxyl group can chelate the aluminum metal ions in the system, thereby forming a protective layer for the PA66 chain and reducing the possibility of its heat discoloration. However, the carbon chain of the unsaturated organic dibasic acid used will affect the introduction of the carboxyl group and the protective effect of the carboxyl group on the carbon atom at the α position of the amide group. After experiments, the inventors preferred unsaturated organic dibasic acids such as 2-propyl-2-butenedioic acid, 4-ethyl-2-pentenedioic acid, 3-hexenedioic acid, 5-methyl-2-hexenedioic acid, 3-methyl-2-hexenedioic acid, 4-isopropyl-2-hexenedioic acid, and 5-methyl-2-heptenedioic acid as modification agents.
[0018] The preparation method of the halogen-free flame retardant and heat-resistant color-changing nylon described above comprises the following steps: using a high-speed mixer to fully stir the modified PA66 resin and the modified glass fiber for 2-3 hours, then adding a halogen-free flame retardant compound, an antioxidant, a heat stabilizer and a high-temperature resistant color powder, and continuing to stir for 1-2 hours to make a uniform mixed material, and finally using an injection molding machine to injection mold it at 250-280°C to obtain the halogen-free flame retardant and heat-resistant color-changing nylon.
[0019] In some embodiments of the present invention, the rotation speed of the high-speed stirrer is 300 r / min.
[0020] Beneficial effects: Compared with the prior art, the present invention uses unsaturated organic dibasic acid to perform addition modification on PA66-6T copolymer, and the obtained modified PA66 resin is used in combination with a halogen-free flame retardant compound. On the one hand, a large number of phosphorus-based free radicals generated by thermal decomposition of ammonium polyphosphate and aluminum hypophosphite are combined with highly active free radicals in the air to generate flame-retardant compounds, which promotes the formation of the combustion carbon layer of PA66-6T and isolates oxygen and heat. At the same time, the added aluminum oxide can make the carbon layer complete and dense, further improving the flame retardant properties of the material; on the other hand, copolymerization modification is used to reduce the proportion of adjacent methylene groups of amide groups in nylon, and then with the help of the introduced carboxyl group, aluminum ions are chelated to protect the methylene hydrogen atoms on the main chain, greatly reducing the thermal discoloration of nylon. In addition, the copolymerization modification of PA66 increases the content of benzene rings, thereby increasing the notched impact strength of the PA66-6T copolymer. DETAILED DESCRIPTION
[0021] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0022] The following is an exemplary description of the preparation process of the modified PA66 resin used in the examples: Modified PA66 resin #1 S1: Weigh 16.6g (0.1mol) of terephthalic acid and 146g (1mol) of adipic acid into a reactor, add deionized water, control the temperature of the reactor at 30°C, then dissolve 127.6g (1.1mol) of hexamethylenediamine in deionized water, heat to an isothermal state with the reactor, add it into the reactor and react for 30min; S2: After the reaction is completed, hot filtration is performed, and the filtrate is subjected to rotary evaporation until crystals are precipitated. After multiple recrystallizations and water washing, the solid sample is placed in a vacuum oven and dried at 100° C. to obtain a PA66-6T copolymer; the surface of the obtained PA66-6T copolymer is cleaned and impurities are removed; S3: In another reactor, ultrapure water, the treated PA66-6T copolymer, and a mixture of sulfuric acid and potassium persulfate were added, and after stirring and mixing, 2-propyl-2-butenedioic acid was added to make the concentration of 2-propyl-2-butenedioic acid in the reaction system be 1.6 mol / L. The reaction was carried out at 50°C for 1 hour, and sulfuric acid and potassium persulfate were added again to make the concentration of sulfuric acid in the reaction system be 0.5 mol / L and the concentration of persulfate ions be 10 mmol / L. The reaction was stopped after 30 hours, and the mother liquor in the reaction system was filtered out. The obtained solid was extracted with boiling water for 2.5 hours, and the clear liquid was filtered out again. The obtained product was vacuum dried to obtain the modified PA66 resin #1.
[0023] Modified PA66 resin #2 S1: Weigh 33.2g (0.2mol) of terephthalic acid and 146g (1mol) of adipic acid into a reactor, add deionized water, control the temperature of the reactor at 45°C, then dissolve 139.2g (1.2mol) of hexamethylenediamine in deionized water, heat to an isothermal state with the reactor, add it into the reactor and react for 40min; S2: After the reaction is completed, hot filtration is performed, and the filtrate is subjected to rotary evaporation until crystals are precipitated. After multiple recrystallizations and water washing, the solid sample is placed in a vacuum oven and dried at 100° C. to obtain a PA66-6T copolymer; the surface of the obtained PA66-6T copolymer is cleaned and impurities are removed; S3: In another reactor, ultrapure water, the treated PA66-6T copolymer, and a mixture of sulfuric acid and potassium persulfate were added, and 5-methyl-2-hexenedioic acid was added after stirring and mixing evenly, so that the concentration of 5-methyl-2-hexenedioic acid in the reaction system was 1.9 mol / L. The reaction was carried out at 53° C. for 1 hour, and sulfuric acid and potassium persulfate were added again, so that the concentration of sulfuric acid in the reaction system was 0.55 mol / L, and the concentration of persulfate ions was 15 mmol / L. The reaction was stopped after 35 hours, and the mother liquor in the reaction system was filtered out. The obtained solid was extracted with boiling water for 2.5 hours, and the clear liquid was filtered out again. The obtained product was vacuum dried to obtain the modified PA66 resin #2.
[0024] Modified PA66 resin #3 S1: Weigh 49.8g (0.3mol) of terephthalic acid and 146g (1mol) of adipic acid into a reactor, add deionized water, control the temperature of the reactor at 60°C, then dissolve 150.8g (1.3mol) of hexamethylenediamine in deionized water, heat to an isothermal state with the reactor, add it into the reactor and react for 45min; S2: After the reaction is completed, hot filtration is performed, and the filtrate is subjected to rotary evaporation until crystals are precipitated. After multiple recrystallizations and water washing, the solid sample is placed in a vacuum oven and dried at 100° C. to obtain a PA66-6T copolymer; the surface of the obtained PA66-6T copolymer is cleaned and impurities are removed; S3: In another reactor, ultrapure water, the treated PA66-6T copolymer, and a mixture of sulfuric acid and potassium persulfate were added, and 5-methyl-2-heptenedioic acid was added after stirring and mixing evenly, so that the concentration of 5-methyl-2-heptenedioic acid in the reaction system was 2.2 mol / L. The reaction was carried out at 57° C. for 1.5 h, and sulfuric acid and potassium persulfate were added again, so that the concentration of sulfuric acid in the reaction system was 0.6 mol / L, and the concentration of persulfate ions was 20 mmol / L. The reaction was stopped after 40 h, and the mother liquor in the reaction system was filtered out. The obtained solid was extracted with boiling water for 3 h, and the clear liquid was filtered out again. The obtained product was vacuum dried to obtain the modified PA66 resin #3.
[0025] Modified PA66 resin #4 The preparation process is similar to that of modified PA66 resin #3, except that the unsaturated organic dibasic acid used is 3,7-dimethyl-2-octenedioic acid.
[0026] Example 1 40% modified PA66 resin #1 and 20% modified glass fiber were fully stirred for 2 hours using a high-speed mixer, and then 30% halogen-free flame retardant compound, 3% antioxidant 168, 3% barium stearate and 4% cobalt blue pigment were added, and stirring was continued for 1 hour to make a uniform mixed material, and finally it was injection molded at 250°C using an injection molding machine to obtain the halogen-free flame retardant and heat-resistant color-changing nylon.
[0027] The preparation process of the modified glass fiber is as follows: deionized water, anhydrous ethanol and aminosilane coupling agent KH791 are mixed in a mass ratio of 100:100:2 to prepare a surface modification liquid; the surface modification liquid is loaded into an ultrasonic disperser, and introduced into the glass fiber for ultrasonic dispersion for 1 hour in a mass ratio of the surface modification liquid to the glass fiber of 10:1; the treated glass fiber is taken out, rinsed with deionized water, and dried.
[0028] The halogen-free flame retardant compound is prepared by mixing ammonium polyphosphate, aluminum hypophosphite and aluminum oxide in a ratio of 5:8:1.
[0029] Example 2 50% of modified PA66 resin #2 and 15% of modified glass fiber were fully stirred for 2.5 hours using a high-speed mixer, and then 25% of a halogen-free flame retardant compound, 3% of an antioxidant 1076, 2% of barium palmitate and 5% of a cobalt green pigment were added, and stirring was continued for 1 hour to prepare a uniform mixed material, and finally the mixture was injection molded at 260°C using an injection molding machine to obtain the halogen-free flame retardant and heat-resistant color-changing nylon.
[0030] The preparation process of the modified glass fiber is as follows: deionized water, anhydrous ethanol and aminosilane coupling agent KH550 are mixed in a mass ratio of 100:100:3 to prepare a surface modification liquid; the surface modification liquid is loaded into an ultrasonic disperser, and introduced into the glass fiber for ultrasonic dispersion for 1.5 hours according to a mass ratio of the surface modification liquid to the glass fiber of 11:1; the treated glass fiber is taken out, rinsed with deionized water, and dried.
[0031] The halogen-free flame retardant compound is prepared by mixing ammonium polyphosphate, aluminum hypophosphite and aluminum oxide in a ratio of 5:8:1.5.
[0032] Example 3 70% of modified PA66 resin #3 and 10% of modified glass fiber were fully stirred for 3 hours using a high-speed mixer, and then 15% of a halogen-free flame retardant compound, 1% of an antioxidant 1076, 1% of barium laurate and 3% of a cobalt green pigment were added, and stirring was continued for 2 hours to make a uniform mixed material. Finally, an injection molding machine was used to perform injection molding at 280°C to obtain the halogen-free flame retardant and heat-resistant color-changing nylon.
[0033] The preparation process of the modified glass fiber is as follows: deionized water, anhydrous ethanol and aminosilane coupling agent APS are mixed in a mass ratio of 100:100:3 to prepare a surface modification liquid; the surface modification liquid is loaded into an ultrasonic disperser, and introduced into the glass fiber for ultrasonic dispersion for 1 hour according to a mass ratio of the surface modification liquid to the glass fiber of 12:1; the treated glass fiber is taken out, rinsed with deionized water, and dried.
[0034] The halogen-free flame retardant compound is prepared by mixing ammonium polyphosphate, aluminum hypophosphite and aluminum oxide in a ratio of 5:8:2.
[0035] Example 4 Similar to Example 3, except that the modified PA66 resin used is modified PA66#4.
[0036] Comparative Example 1 Similar to Example 3, the difference is that the modified PA66 resin used is only PA66-6T copolymer, and no unsaturated organic dibasic acid is grafted.
[0037] Comparative Example 2 Similar to Example 3, the difference is that the resin used is only PA66 resin, and neither PA6T copolymerization modification nor unsaturated organic dibasic acid grafting is performed.
[0038] Comparative Example 3 Similar to Example 3, except that aluminum oxide is not added to the halogen-free flame retardant compound used.
[0039] Performance Testing Flame retardant grade: According to GB / T2408-2008, the UL94 flame retardant grade of the sample is tested using a vertical combustion tester; Thermal oxygen aging: In a constant temperature blast thermal oxygen aging box, perform thermal oxygen accelerated aging test according to GB / T7141-1992. Take out the samples after 120 hours and test the yellowness index (YI) of the samples according to GB2409-80. Notched impact strength: refer to GB / T1843-2008 test.
[0040] The test results are detailed in Table 1:
[0041] From the results in Table 1, it can be seen that in the present invention, the structure of the grafted unsaturated organic dibasic acid in the modified PA66 resin has an important influence on the thermal discoloration of the final nylon material: in Example 4, the increase in the carbon chain of the unsaturated organic dibasic acid used leads to an increase in the yellow index of the obtained nylon material, which also indicates that the thermal discoloration resistance of the material is weakened. The results of Comparative Examples 1-3 further prove the importance of the two-step modification of PA66 resin and the presence of aluminum oxide in improving the flame retardancy, thermal discoloration resistance and notched impact strength of nylon materials.
Claims
1. A halogen-free flame-retardant heat-resistant color-changing nylon, characterized in that: The invention comprises the following raw materials in percentage by mass: 40-77% of modified PA66 resin, 10-20% of modified glass fiber, 10-30% of halogen-free flame retardant compound, 1-3% of antioxidant, 1-3% of heat stabilizer and 1-5% of high temperature resistant color powder; wherein the modified PA66 resin is a polymer obtained by modifying PA66-6T copolymer with unsaturated organic dibasic acid, and the halogen-free flame retardant compound comprises ammonium polyphosphate, aluminum hypophosphite and aluminum oxide.
2. The halogen-free flame-retardant heat-resistant color-changing nylon according to claim 1, characterized in that: The preparation method of the modified PA66 resin comprises the following steps: S1: Weigh terephthalic acid and adipic acid and put them into a reactor, add deionized water, control the temperature of the reactor at 30-60°C, then dissolve hexamethylenediamine in an equal molar amount to the two dibasic acids in deionized water, heat to an isothermal state with the reactor, add it into the reactor and react for 30-45 minutes; S2: After the reaction is completed, hot filtration is performed, and the filtrate is taken for rotary evaporation until crystals are precipitated. After multiple recrystallizations and water washing, the solid sample is placed in a vacuum oven for drying to obtain a PA66-6T copolymer; the surface of the obtained PA66-6T copolymer is cleaned and impurities are removed; S3: Add ultrapure water, the treated PA66-6T copolymer, and the initiator into another reactor, stir and mix well, then add the unsaturated organic dibasic acid, react for 1-1.5h, add the initiator again, and stop the reaction after the predetermined time, filter out the mother liquor in the reaction system, extract the obtained solid with boiling water for 2.5-3h, filter out the clear liquid again, and vacuum dry the obtained product to obtain the modified PA66 resin.
3. The halogen-free flame-retardant heat-resistant color-changing nylon according to claim 2, characterized in that: The initiator in S3 is a mixture of sulfuric acid and potassium persulfate, and in the reaction system, the sulfuric acid concentration is 0.5-0.6 mol / L, and the persulfate concentration is 10-20 mmol / L.
4. The halogen-free flame-retardant heat-resistant color-changing nylon according to claim 2, characterized in that: The unsaturated organic dibasic acid described in S3 is one of 2-propyl-2-butenedioic acid, 4-ethyl-2-pentenedioic acid, 3-hexenedioic acid, 5-methyl-2-hexenedioic acid, 3-methyl-2-hexenedioic acid, 4-isopropyl-2-hexenedioic acid, and 5-methyl-2-heptenedioic acid, and its concentration in the system is 1.6-2.2 mol / L.
5. The halogen-free flame-retardant heat-resistant color-changing nylon according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: mixing deionized water, anhydrous ethanol and aminosilane coupling agent in a mass ratio of 100:100:2-4 to prepare a surface modification liquid; loading the surface modification liquid into an ultrasonic disperser, introducing it into the glass fiber for ultrasonic dispersion for 1-2 hours; taking out the treated glass fiber, rinsing it with deionized water, and drying it to obtain the modified glass fiber.
6. The halogen-free flame-retardant heat-resistant color-changing nylon according to claim 5, characterized in that: The mass ratio of the surface modification liquid to the glass fiber is 10-12:
1.
7. The halogen-free flame-retardant and heat-resistant color-changing nylon according to claim 1, characterized in that: In the halogen-free flame retardant compound, the mass ratio of ammonium polyphosphate, aluminum hypophosphite and aluminum oxide is 5:8:1-2.
8. The halogen-free flame-retardant heat-resistant color-changing nylon according to claim 1, characterized in that: The heat stabilizer includes at least one of barium stearate, barium palmitate, barium oleate, barium laurate and barium myristate.
9. The halogen-free flame-retardant heat-resistant color-changing nylon according to claim 1, characterized in that: The high temperature resistant toner contains at least one of a cobalt blue pigment and a cobalt green pigment.
10. The method for preparing the halogen-free flame-retardant and heat-resistant color-changing nylon according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: using a high-speed mixer to fully stir the modified PA66 resin and the modified glass fiber for 2-3 hours, then adding a halogen-free flame retardant compound, an antioxidant, a heat stabilizer and a high-temperature resistant color powder, and continuing to stir for 1-2 hours to prepare a uniform mixed material, and finally using an injection molding machine to perform injection molding at 250-280° C. to obtain the halogen-free flame retardant and heat-resistant color-changing nylon.
Citation Information
Patent Citations
Hexamethylene diamine adipate fibre-adding anti-flaming modified material and preparation method thereof
CN101165097A
Glass fiber reinforced halogen-free flame-retardant PA66 and preparation thereof
CN101503569A
High glow-wire and fiber halogen-free flame-retardant nylon 66 material and preparation method thereof
CN102424722A
Halogen-free flame-retardant long glass fiber enhanced nylon 6T composite material and preparation method thereof
CN106398191A
Halogen-free inflaming-retarding high-temperature-resistance anti-yellowing PA6 / PA66 composite material and preparation method thereof
CN107337925A
